2013
DOI: 10.1371/journal.pgen.1003503
|View full text |Cite
|
Sign up to set email alerts
|

HDAC7 Is a Repressor of Myeloid Genes Whose Downregulation Is Required for Transdifferentiation of Pre-B Cells into Macrophages

Abstract: B lymphopoiesis is the result of several cell-commitment, lineage-choice, and differentiation processes. Every differentiation step is characterized by the activation of a new, lineage-specific, genetic program and the extinction of the previous one. To date, the central role of specific transcription factors in positively regulating these distinct differentiation processes to acquire a B cell–specific genetic program is well established. However, the existence of specific transcriptional repressors responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 36 publications
(54 reference statements)
0
50
0
Order By: Relevance
“…4, C-F), we cannot discount the possibility that inhibition of other class IIa Hdacs contributes to these effects. A recent study also showed that Hdac7 downregulation was required for trans-differentiation of B cells into macrophages and for optimal acquisition of TLR4 responses (59). This suggests that specific Hdac7 isoforms may have distinct functions in mature macrophages versus during myeloid development.…”
Section: Hdac7 (Ensembl Code Enst00000427332mentioning
confidence: 95%
“…4, C-F), we cannot discount the possibility that inhibition of other class IIa Hdacs contributes to these effects. A recent study also showed that Hdac7 downregulation was required for trans-differentiation of B cells into macrophages and for optimal acquisition of TLR4 responses (59). This suggests that specific Hdac7 isoforms may have distinct functions in mature macrophages versus during myeloid development.…”
Section: Hdac7 (Ensembl Code Enst00000427332mentioning
confidence: 95%
“…In this process, C/EBPα expression in pre-B cells coordinates the acquisition of the macrophage-specific gene-expression programme leading to the generation of functional macrophages. It has been demonstrated that HDAC7 has a role in repressing macrophage-specific genes, and its expression is strongly downregulated during C/EBPα-mediated transdifferentiation, allowing the induction of the macrophage-specifying programme 49 .…”
Section: Yamanaka Factorsmentioning
confidence: 99%
“…HDAC9 was reported to induce inflammatory gene expression in macrophages and prevent polarization to anti-inflammatory M2 phenotype 52 . With regards to adaptive immunity, HDAC7 and HDAC2 have been reported to maintain B cell and CD4+ T cell identity, respectively 53, 54 . Interestingly, HDAC9 and HDAC3 were shown to control CD4 + Foxp3 + T regulatory (Treg) cell development and function 55, 56 .…”
Section: Hdacs and Inflammationmentioning
confidence: 99%